2006
DOI: 10.1016/j.physd.2005.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of moving discrete breathers with vacancies

Abstract: In this paper a Frenkel-Kontorova model with a nonlinear interaction potential is used to describe a vacancy defect in a crystal. According to recent numerical results [Cuevas et al. Phys. Lett. A 315, 364 (2003)] the vacancy can migrate when it interacts with a moving breather. We study more thoroughly the phenomenology caused by the interaction of moving breathers with a single vacancy and also with double vacancies. We show that vacancy mobility is strongly correlated with the existence and stability proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Vacancies have been seen to move in simulations [17,18] but this has not yet been verified in specific models for muscovite.…”
Section: Moving Vacanciesmentioning
confidence: 94%
“…Vacancies have been seen to move in simulations [17,18] but this has not yet been verified in specific models for muscovite.…”
Section: Moving Vacanciesmentioning
confidence: 94%
“…The first studies of the DB interaction with the vacancy were carried out in the framework of a 1D Frenkel-Kontorova model [30,31]. It has been shown that a moving DB can cause vacancy migration.…”
Section: Dbs and Crystal Lattice Defectsmentioning
confidence: 99%
“…It has been shown that a moving DB can cause vacancy migration. Moreover, a significant role in this process is played by a nonlinear vibrational mode localized on the atom adjacent to the vacancy [31]. In frame of the same model migration of interstitial atom due to the interaction with moving DB has been studied [32].…”
Section: Dbs and Crystal Lattice Defectsmentioning
confidence: 99%
“…The first studies of the DB interaction with the vacancy were carried out in the framework of a one-dimensional Frenkel-Kontorova model with nonlinear interaction between particles [74,75]. It has been shown that a moving DB can cause vacancy migration.…”
Section: Interaction Of Db With Lattice Defectsmentioning
confidence: 99%
“…It has been shown that a moving DB can cause vacancy migration. Moreover, a significant role in this process is played by a nonlinear vibrational mode, localized on the atom adjacent to the vacancy [75]. In frame of the same model the interaction of mobile DB with the interstitial atom has been investigated [76].…”
Section: Interaction Of Db With Lattice Defectsmentioning
confidence: 99%